Istanbul: the making of a global city between East and West - Ozgur Sayin (2018)
From the outset global cities have been primarily seen as outcomes of changes in global economic capitalism. This has led to critical responses arguing for the need to consider more centrally the role of politics in global city formation, and in particular the need to critically analyse city-state relations in varying geographical contexts. Three dominant strands of critique have emerged: a literature on state rescaling (primarily based on experiences of North American and Western European cities), a literature on developmental states (on East Asian cities) and a literature on postcolonial urban theory (primarily on cities in the Global South). Although these approaches all argue for a re-focusing on the role of the political in global city formation, they do not easily fit other geographical and geopolitical contexts. This thesis aims to contribute to the debate by focusing on the case of Istanbul as Turkey s emerging global city. Based on semi-structured interviews, this research challenges some key assumptions of global cities research, state rescaling approach, developmental approach and postcolonial urban theory through the case of Istanbul. It also provides a critical conceptual understanding of Istanbul s globalisation, argues the role of actors in global city making and will demonstrate that contrary to what is generally claimed in the literature, the relationship between Istanbul (city) and Turkey (state) could be assessed as more harmonious rather than tension-filled. Furthermore, the research goes beyond revealing the points where Istanbul conforms or does not conform to the existing approaches, and addresses the very recent academic debates between those who believe that we need new theories to understand the dynamics and impacts of the actual global urbanisation and those who suggest that instead of calling for new theories there is a need to examine and improve the existing approaches. To do that, my research develops an alternative conceptualisation -- the in-between city - that might cover the cities located in the region spreading from Eastern Europe to Central Asia. The argument behind this concept is that owing to their intersectional positions between East and West, and the continual links between their imperial and global periods, cities such as Istanbul, Vienna, Budapest, St. Petersburg or Moscow, present more hybrid characteristics in comparison to the cities categorised by the existing approaches.